TEORI PERKEMBANGAN PESERTA DIDIK - Nur Ganti Ritonga; Rosmaini Siregar; Husnul Hadi Dalimunthe; Rahmah Hadi Dalimunthe (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this study is to find out the theory of student development. This type of research is library research. This research makes Library materials as its main data source. The theory of psychoanalysis is a form of flow, one of the theories that discusses the nature and development of personality forms owned by humans. One of the factors that determine the progress and retreat of an organization is the existence of human resources who have quality abilities both in knowledge, skills, and attitudes, will make an organization easy to achieve the goals set. Because human resources are the key that moves the wheels of the organization so that it usually runs dynamically, the main elements in theory are motivation, emotions, and other aspects of personality. This article will examinedevelopmental theory, Sigmund Freud's structure of human personality, Erik-Erikson's human personality development, Abraham Maslow's hierarchy of needs, Buhler Rogers, Charlotte's self-concept. Through this paper it is necessary to instill motivation in the development of students.